Temperature-regulated control of toxic genes in the methylerythritol phosphate pathway of synechococcus sp. PCC 7002 cyanobacteria - Raebel, Meghan (My University, 2018)
Cyanobacteria are microalgae that have the potential to become a frontrunner for clean energy and renewable bioproducts. These green bacteria efficiently harvest sunlight and atmospheric CO2, to produce a variety of organic compounds, including isoprene, a precursor for synthetic rubber, pharmaceuticals, and Bio-Jet fuel. Cyanobacteria, such as the marine strain, Synechococcus sp. PCC 7002, replicate quickly, can be grown in wastewaters, and need not compete with food crops for arable land. Additionally, cyanobacteria contain the methyl erythritol phosphate (MEP) pathway, by which isoprene can be produced. Our group has engineered isoprene production in Synechococcus cyanobacteria (US patent 9,382,554) and we are working to enhance this technology toward commercialization. One strategy for increased isoprene yields involves introducing optimized genes for the MEP pathway, but some of these genes or their products may be toxic and prevent cyanobacterial growth. Thus, the objective of this research is to develop a means of controlling such genes so that they are expressed only after the cyanobacterial culture has reached a high density. One means of control is through genetic promoters and regulators. One such regulator is cI857-pR, a temperature-regulated repressorpromoter from a bacterial virus. We believe this will provide a means to regulate gene expression and determine whether introduced genes are toxic. In this thesis project, I have created genetic fusions of this regulator to genes within the MEP pathway, and have demonstrated an increase in isoprene production up to three times the rate observed in a control strain. Understanding how these gene products and their regulation works in the cyanobacteria will inform us how to more effectively insert enhanced genes for the MEP pathway, control their activity, and develop strains with enhanced isoprene yields.
Keywords: isoprene; cyanobacteria--biotechnology; cyanobacteria